Analysis of Islamic Financial Literacy and Islamic Fintech Adoption on Financial Inclusion and Business Performance of Halal MSMEs in Banten Province - Sudarmanto, Eko; Barus, Irwan Irawadi; Kaswoto, Junet; Pamikatsih, Mutia (West Science Journal Economic and Entrepreneurship, 2026)
The development of Islamic financial services and digital financial technology provides significant opportunities to strengthen financial inclusion and improve the competitiveness of halal Micro, Small, and Medium Enterprises (MSMEs). However, limited financial knowledge and restricted access to appropriate financial services remain major challenges faced by many halal MSMEs. This study aims to analyze the influence of Sharia Financial Literacy and Sharia Fintech Adoption on Financial Inclusion and Business Performance of Halal MSMEs in Banten Province. This research employs a quantitative explanatory approach using a cross-sectional survey method. Data were collected from 155 halal MSME actors in Banten Province using a structured questionnaire measured with a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that Sharia Financial Literacy has a positive and significant effect on Financial Inclusion, while Sharia Fintech Adoption also positively influences Financial Inclusion. Furthermore, Sharia Financial Literacy, Sharia Fintech Adoption, and Financial Inclusion, significantly contribute to improving MSME Business Performance. The mediation analysis confirms that Financial Inclusion partially mediates the relationship between Sharia Financial Literacy and Business Performance, as well as between Sharia Fintech Adoption and Business Performance. These findings highlight that strengthening Islamic financial knowledge and accelerating the adoption of Sharia-based digital financial services are essential strategies for improving financial accessibility and sustainable growth of halal MSMEs. The study provides practical implications for policymakers, Islamic financial institutions, and fintech providers in developing inclusive financial ecosystems that support halal MSME development.
Keywords: Sharia Financial Literacy; Sharia Fintech Adoption; Financial Inclusion; Business Performance; Halal MSMEs